Introduction: Into the Air - Liam Cole Young; Chris Russill; Hannah Dick (Media Theory, 2022)
In this introduction to the Into the Air special issue of Media Theory, the editors reflect on the resonances and rhythms of John Durham Peters’ Speaking into the Air (1999). We consider what was in the air at the time of the book’s original publication, and during our time assembling this special issue. Drawing on publication and marketing materials from the book, as well as work in cultural studies, Black studies, and postcolonial theory, we expand on what we see as the generous possibilities and potential for thinking with this text across historical junctures and against conventional understandings of civilizational time. We also introduce the key themes of this special issue and provide a brief overview of the contributions.